Restructuring and competitiveness in the transition process: Evidence from an Eastern German firm panel - Katja Gerling; Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
In a transforming economy there is a common legacy of most companies: their low competitiveness as the result of an obsolete capital stock and overmanning, insufficient product quality that does not satisfy demand, distorted specialization patterns, high and partly ill-designed integration, suboptimal size and inadequate management capacities. Restructuring companies is therefore a challenging task. The paper examines the painful adjustment process in eastern German manufacturing against the background of the unpleasant trade-off between the pace of wage increase and the level of transfer payments to spur investment and to finance consumption. The core question is how the performance of companies has developed with regard to ownership structure, firm size and industry. The paper - first, analyses the dilemma from a theoretical point of view, - second, highlights the economic repercussions of the companies' adjustment behaviour to be mirrored in the data, and - third, draws the conclusions and provides some suggestions for further analysis. Data used in the paper mainly come from a sample of firms under investigation of the Deutsches Institut fur Wirtschaftsforschung (DIW), Berlin, since 1991.
Keywords: P52; 330; Reorganisation; Produktivität; Internationaler Wettbewerb; Eigentümerstruktur; Betriebsgröße; Eigenkapital; Industrieller Strukturwandel; Öffentlicher Transfer; Neue Bundesländer